Cemented versus screw‐retained posterior implant‐supported single crowns: A 24‐month randomized controlled clinical trial. Issue 12 (3rd October 2021) - Wolfart, Stefan; Rittich, Anne; Groß, Karin; Hartkamp, Oliver; von der Stück, Annabelle; Raith, Stefan; Reich, Sven
Abstract: Objectives: To compare the incidence of biological and technical complications of cemented and screw‐retained monolithic lithium‐disilicate implant‐supported posterior single crowns. Material and Methods: Forty‐one subjects with a total of 56 implants received randomly allocated 28 cemented and 28 screw‐retained crowns. In the screw‐retained group, monolithic lithium‐disilicate restorations were luted to titanium bases extraorally. In the cemented group, monolithic lithium‐disilicate crowns were cemented on individualized titanium abutments intraorally. All restorations were examined according to modified FDI criteria within 2 weeks of inserting the crowns (baseline) and after 12 ( n = 46) and 24 ( n = 43) months. Bone loss was evaluated by standardized radiographs at baseline and 12 months. Results: After 12 months, the incidence of mucositis (positive bleeding on probing) was 14.2% (screw‐retained) and 17.9% (cement‐retained). The gingival and plaque index and a mean marginal bone loss between 0.03–0.15 mm showed no significant difference between the groups. In the cemented group, cement residues were detected at baseline at two restorations (6.9%) by radiographic examination. A complete digital workflow was realized in most cases (85.7%). At 24 months, no restoration had failed, and no chipping of the ceramic had occurred. In the screw‐retained group, screw loosening occurred in one implant. In both groups, there was obvious deterioration in the quality of 32% of the occlusal and of 18% of the proximal contact points. Conclusions: The type of retention mode of monolithic implant‐retained lithium‐disilicate posterior crowns had no influence on the biological and technical complication rate.